1994
DOI: 10.1123/ssj.11.3.298
|View full text |Cite
|
Sign up to set email alerts
|

“Battling” Gendered Language: An Analysis of the Language Used by Sports Commentators in a Televised Coed Tennis Competition

Abstract: In this study, we examine how sports commentators minimized women’s athletic participation, abilities, and achievements in the 1992 televised “Battle of the Champions” tennis competition between Martina Navratilova and Jimmy Connors. Using content analysis, we found clear differences in naming practices, adjective and adverb use, amount and type of praise and criticism, and character flaws attributed to the players. In the unique case of male versus female athletic competition it also becomes apparent that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 10 publications
2
35
0
2
Order By: Relevance
“…With so few women in interscholastic athletics, those women in leadership roles may find it difficult to overcome the bias some men and women may hold against them regarding their managerial prowess just as seen by women in managerial roles in the business community (Deal and Stevenson 1998). When television and other forms of media trivialize women's sports as being feminine (Halbert and Latimer 1994), perceptions are formed which reinforce the notion that men rather than women are better suited to be coaches. This lack of representation by women in high visibility leadership roles, such as coaches and athletic directors reinforces negative perceptions towards women being leaders, feeding the status quo.…”
Section: Discussionmentioning
confidence: 90%
“…With so few women in interscholastic athletics, those women in leadership roles may find it difficult to overcome the bias some men and women may hold against them regarding their managerial prowess just as seen by women in managerial roles in the business community (Deal and Stevenson 1998). When television and other forms of media trivialize women's sports as being feminine (Halbert and Latimer 1994), perceptions are formed which reinforce the notion that men rather than women are better suited to be coaches. This lack of representation by women in high visibility leadership roles, such as coaches and athletic directors reinforces negative perceptions towards women being leaders, feeding the status quo.…”
Section: Discussionmentioning
confidence: 90%
“…Some have suggested that gender roles can then be reinforced through their assimilation during the viewing of televised sporting events, and this can furthermore lead to an individual's increased belief in these stereotypes outside of sports (Stice et al 1994). These beliefs in the differences between men and women, and in this context between masculine and feminine sports, are constructs of social reality that reinforce societal inequities between genders, which include the concepts of masculine dominance and feminine inferiority (Eastman and Billings 2000;Halbert and Latimer 1994;Spender 1980); in sports, men's events are considered a "must see" and women's sports are often considered "nonevents" (Messner et al 1996).…”
Section: Review Of Literaturementioning
confidence: 96%
“…It is incredibly rare to hear a male athlete referred to as a 'boy.' In the sport of tennis, terms such as 'girl' have been showed to be used in 52.7% of the commentating, while only 7.8% of the coverage referred to the male athletes as 'boys' (Halbert and Latimer 1994;Messner et al 1993).…”
Section: Review Of Literaturementioning
confidence: 97%
See 1 more Smart Citation
“…Often this differential treatment can be seen in the form of sexist language; language exists within sports media that serves to reiterate gender-specific stereotypes and expectations (Bissell & Duke, 2007). As noted above, positions of sports writers and commentators are typically held by males, and previous studies affirm language used for both male and female athletes emphasizes gender inequalities (Duncan & Hasbrook, 1988;Halbert & Latimer, 1994). Though such studies focus on gender and sexist language, the same principles can be applied to language that showcases a strong nationalistic bias by using the principles of in-group and out-group discourse.…”
Section: Nationalism Bias In Sportsmentioning
confidence: 99%